Dissent with love
1 online resource (xiii, 190 pages).
Keywords: "This book presents a unique rendering of love in South Asia by reading love through the specific lens of dissent. It presents multiple articulations of dissenting love in contemporary South Asia including negotiations with parents to assert choice of partner, migration, elopement, live-in relationships, singlehood, 'new' ideas of masculinities, and embracing diverse sexual identities. It studies these forms of dissent in the context of changing legal discourses, impact of media in everyday life, and transforming social attitudes. As such, this book is the first of its kind to analyse the myriad ways in which love and dissent constitute each other shaping the social, political, and cultural mores and movements of South Asia. The contributions are based on ethnographic research cutting across diverse religious, ethnic, and gender and sexual identities of South Asia. Part of the Social Movements and Transformative Dissent series, this book will be of interest to students and researchers of sociology, anthropology, history, geography, political science, gender studies, and media studies. It will also appeal to academics who study South Asia with a special focus on love, intimacy, sexuality, marriage, migration, history, politics and media"--